A reproducible analytical system based on the multi-component analysis of triterpene acids in Ganoderma lucidum. (June 2015) - Da, Juan; Cheng, Chun-Ru; Yao, Shuai; Long, Hua-Li; Wang, Yan-Hong; Khan, Ikhlas A.; Li, Yi-Feng; Wang, Qiu-Rong; Cai, Lu-Ying; Jiang, Bao-Hong; Liu, Xuan; Wu, Wan-Ying; et al.
Graphical abstract: Ten triterpenes in Ganoderma lucidum were quantitatively determined using ultra performance liquid chromatography, with ganoderic acid A serving as the single reference standard. Stable system parameters were established. Highlights: An UPLC–SSDMC method was established for ganoderic and ganoderenic acids using a single reference standard. Conversion factors of ten triterpenes in Ganoderma lucidum were validated. An innovative gradient elution method was developed. Major parameters of the analytical procedure were validated to be stable. Abstract: Ultra-performance liquid chromatography (UPLC) and Single Standard for Determination of Multi-Components (SSDMC) are becoming increasingly important for quality control of medicinal herbs; this approach was developed for Ganoderma lucidum . Special attention was necessary for the appropriate selection of markers, for determining the reproducibility of the relative retention times (RRT), and for the accuracy of conversion factors (F). Finally, ten components were determined, with ganoderic acid A serving as single standard. Stable system parameters were established, and with successful resolution of those issues, this analytical method could be used more broadly.